A Comprehensive Review on Studies of Flow Characteristics in Horizontal Tube Falling Film Heat Exchangers - Zhenchuan Wang; Meijun Li (Energies)
The horizontal tube falling film heat exchangers (HTFFHEs), which exhibit remarkable advantages such as high efficiency in heat and mass transfer, low resistance, and a relatively simple structural configuration, have found extensive applications. Complex flow phenomena and the coupled processes of heat and mass transfer take place within it. Given that the heat and mass transfer predominantly occur at the gas-liquid interface, the flow characteristics therein emerge as a significant factor governing the performance of heat and mass transfer. This article elaborates on the progress of experimental and simulation research approaches with respect to flow characteristics. It systematically reviews the influence patterns of various operating parameters, namely parameters of gas, solution and internal medium, as well as structural parameters like tube diameter and tube spacing, on the flow characteristics, such as the flow regime between tubes, liquid film thickness, and wettability. This review serves to furnish theoretical underpinnings for optimizing the heat and mass transfer performance of the horizontal tube falling film heat exchanger. It is further indicated that the multi-dimensional flow characteristics and their quantitative characterizations under the impacts of different airflow features will constitute the focal research directions for horizontal tube falling film heat exchangers in the foreseeable future.